Multimetallic Porphyrins/Polyoxotungstate Modified Electrodes by Layer-By-Layer Method: Electrochemical, Spectroscopic and Morphological Characterization - Aguirre-Quintana, M; Aguirre-Quintana, M (2012)
Sin Editorial Disponible